A study of the development of the digital ranch - Amanda Spink; Jane Hicks (Information Research: An International Electronic Journal)
A lack of research investigating the role of information and information needs currently hampers improvement in information services to rural industries. This paper provides preliminary findings from the first phase of a project investigating the role of information, including the use of networked information services by the cattle ranching community -- a major information user group in rural environments. Selected findings are reported from a national survey of 1600 cattle ranchers and members of the Red Angus Association of America. Results show the "electronic" or "digital" ranching community is in the early stages of development as "early adopters" begin to use networked information services. Implications are derived for the development of digital libraries for cattle ranchers.